Understanding Radicalization: Terrorist Behavior at odds with Pancasila - Faiz Albar Nasution; Lazuardhi Al Fath Bahari P; Acnes Rajagukguk; Dimas Aditya Pratama; Amelia Siska Dongoran; Maqhfirotul Ainun Naim (Talenta Publisher, 2023)
The dynamics life of society is constantly changing, both positively and negatively. The loss of high moral standards and ideals in society, particularly the implementation of the Pancasila values, can result in negative changes. The growth of radicalism and the frequent occurrence of terrorist actions in Indonesia are two examples of how Pancasila values are eroding. These are some of the goals of this activity: First, spreading knowledge about terrorism, radicalism, and their relationship as they conflict with Pancasila ideals Second, raise people's knowledge and awareness of the risks posed by terrorism and radicalism. Third, promote understanding of radicalism and terrorist acts through socialization. Students in class XII IPS 3 SMA Negeri 1 Medan will be exposed to information on radicalism, terrorism, and other behaviors that are against Pancasila ideals through lectures and discussions. Results from socialization activities revealed that pupils had a positive mindset. The socialization participants thought that this exercise could raise knowledge and awareness of the risks associated with radicalization and terrorist acts that are at odds with Pancasila ideals. Evidently, socialization participants are dedicated to making an effort to incorporate Pancasila values into their daily life.